The Exchnge-Rate Question in Europe - Francesco Giavazzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
This paper reviews the arguments for and against monetary unification in Europe, taking into account the recent shift in emphasis in the analysis of exchange-rate regimes.
Keywords: 330